PENJATUHAN SANKSI TERHADAP PELANGGARAN DISIPLIN PEGAWAI NEGERI SIPIL - Surya Permana Putra, I Made; Parsa, I Wayan; Dyah Satyawati, Ni Gusti Ayu (Kertha Semaya : Journal Ilmu Hukum, 2013)
The Civil Servants is a person who work for the government with full of loyalty and obedience to the Pancasila and the 1945 Constitution. The aim of this research is to determine the type of the sanction for the Civil Servant and how the mechanism to impose the sanction. This research is normative legal research using primary and secondary legal materials. The issues in this research are : the type of disciplinary action and the procedure to impose the sanction. The type of disciplinary punishment consisting of disciplined Light, Medium and Heavy. Concerning the procedures for the imposition of disciplinary punishment , it can be concluded that the punishment of the disiplinary sanctions will be imposed based on the stage of the actions. It can be started with the reprimand to termination with no respect as a Civil Servant.
Keywords: Discipline, Civil Servants, Sanctions